Ответы и объяснения

2013-03-26T05:18:51+00:00

(sin²a+1+2cosa+cos²a)/(sina)(1+cosa)=(2+2cosa)/sina(1+cosa)=2(1+cosa)/sina(1+cosa)=2/sina

ИЛИ

sina/(1+cosa)+(1+cosa)/sina-2/sina=0; sina/(1+cosa)+(cosa-1)/sina=0; ((sina)^2+(cosa)^2-1)/(sina(1+cosa))=0;(1-1)/(sina(1+cosa))=0 

Тока не знаю правельно ли это 

Лучший Ответ!
2013-03-26T06:01:49+00:00

Пусть А=2а,

вспомним формулы:

cos2а=cos²a-sin²a = cosA

sin2a=2sina*cosa = sinA

sin²a+cos²a=1 подставим в наше выражение:

1-cosA+sinA = (sin²a+cos²a) - (cos²a-sin²a) + 2sina*cosa=

sin²a+cos²a - cos²a+sin²a + 2sina*cosa=2sin²a + 2sina*cosa=

2sina(sina + cosa), вспомним, что а=А/2, получим ответ:

2sin(А/2) * ( sin(А/2) + cos(А/2) )